CHANGES OF MIDDLE CHILDHOOD STUDENTS’ EMOTIONAL AWARENESS IN SOCIAL COMPETENCE AND AWARENESS INTERVENTION GROUP FOR CHILDREN - Elsiņa, Inese; Svence, Guna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Emotion awareness (EA) is the cornerstone of emotional intelligence, an essential prerequisite for the development of children's social competence. Recent scientific studies have shown that EA has a number of positive psychological outcomes. The main objective of the study was to develop and implement the EA and social competence intervention program for children (N=19, boys n=8 and girls n=11, age8 -9, M=8,05, SD=0,23) and compare the indicators of EA of middle childhood students before and after the realization of the author's program. Additional purpose of the study was the approbation of The Levels of Emotional Awareness Scale for Children (LEAS-C; Bajgar&Lane, 2003) by analysis of its psychometric indicators. In total 13 sessions were carried out during the school year 2013/2014 - from the beginning of November, 2013 until the end of May, 2014. LEAS-C (Bajgar&Lane, 2003) and Children's Personality Questionnaire (CPQ, Porter & Cattel, 1975), observations, interviews, content analysis were used. The study results show the effectiveness of intervention programs, namely, it was found that there was a statistically significant difference between the EA level of children before and after the intervention program (SELF t=- 2,99, p=0,008, OTHER t=- 3,78, p=0,001, TOTAL t=- 3,58 (p=0,002<0,05). The level of EA increased and the quality of emotional vocabulary improved after the intervention program. The LEAS-C version in Latvian language of showed high internal consistency scores and high Inter-Rater Reliability between the two encoders. The paper also carries out detailed analysis of indicators of construct validity.